Palliative radiotherapy for leptomeningeal metastases after photon-based intensity-modulated radiotherapy in a nasopharyngeal cancer patient - Marlina, Yoke S.; Novirianthy, Rima; Beočanin, Anđelija (Narra Sains Indonesia, 2023)
Leptomeningeal metastasis is a rare in nasopharyngeal carcinoma, affecting less than 5% of patients with a poor prognosis. The aim of this case report was to present management of palliative radiotherapy in leptomeningeal metastasis of nasopharyngeal carcinoma patient. A 33-year-old female presented with nasopharyngeal carcinoma with stage III, T3N3M0, WHO type III. The patient has received chemoradiation with photon-based intensity-modulated radiotherapy (IMRT) technique at the dose of 70 Gy in 33 fractions and showed a satisfactory outcome in 12 months follow-up. Later, at 18 months after chemoradiation completion, the patient complained of worsening bilateral sciatic pain, particularly during coughing, with slight limitations in bilateral hip flexion observed during straight leg raises. The whole spine contrast-enhanced magnetic resonance imaging (MRI) examination showed nodular enhancement of leptomeningeal thickening at the T4 level of the spinal cord lower than S3. Palliative radiation therapy utilized a three-dimensional conformal radiation therapy (3D-CRT) technique producing 35 Gy in 14 fractions placed in a field spanning the T4-S3 vertebral bodies. Methotrexate was administered intravenously every two weeks for three cycles to ensure central nervous system penetration. After four months of follow-up, no evidence of disease was found at the primary site and metastatic areas on subsequent physical examination or imaging with MRI and there was satisfactory improvement in neurologic symptoms. In conclusion, leptomeningeal metastases with primary nasopharyngeal carcinoma are rare and typically cause neurological impairments in patients. Hematogenous or cerebrospinal fluid-mediated spread of the cancer is considered the most likely pathway for leptomeningeal dissemination. Strategic modalities, such as radiotherapy with chemotherapy, may improve outcomes in symptoms and quality of life.